PASTORAL KONSELING KEPADA PEREMPUAN KORBAN MARITAL RAPE DI DESA WARUKAPAS MINAHASA UTARA - Gratia Thalia Siwi; Meily Meiny Wagiu; Marde Christian Stenly Mawikere (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2024)
Marital rape is sexual violence that occurs in the domestic realm or more precisely in the personal realm between husband and wife, it is rarely paid attention to by the public so that the victim feels alone and isolated due to the impact that the victim feels because if he tells other people the victim feels this is a serious problem. sensitive and private. So the impact that the victim feels holistically is physical, mental, social and spiritual. holistically so as to be able to reorganize household life properly. This research uses a pastoral counseling case study, the data in this research was obtained through observation, interviews and verbatim with women victims of marital rape in Warukapas Village, North Minahasa. The research results show that women who are victims of marital rape do not yet understand the act of marital rape even though they have experienced it. The causal factors include the husband's uncontrolled behavior and lust due to being influenced by alcohol, there is cultural influence regarding sexual obligations that the wife is expected to comply with, as well as economic dependence so that the victim woman is reluctant to resist her husband's coercion. The impact experienced by victims of sexual violence is mild, such as through verbal abuse through curses from their husbands, to experiencing severe sexual violence such as experiencing beatings, detention and being forced to have sexual relations. In this study, researchers conducted pastoral counseling conversations (PKP) with subjects using an integrative approach to the core subject cases. So it is hoped that the approach and methods in this research can provide recommendations and education to prevent acts of marital rape.